Предмет: Алгебра,
автор: DiAnNa123er
ПОМОГИТЕ ПОЖАЛУЙСТА!!!!!!!!
Докажите неравенство:
(х – 2)² > х (х - 4)
а²+ 1 2 (3а – 4)
DiAnNa123er:
Реши пожалуйста!!!!
Ответы
Автор ответа:
1
^-степень. 1)(x-2)^2>x(x-4)
(х-2)^2=х^2-4х+4
х(х-4)=х^2-4х
2)а²+1≥2(3а-4) а²+1≥6а-8
(х-2)^2=х^2-4х+4
х(х-4)=х^2-4х
2)а²+1≥2(3а-4) а²+1≥6а-8
Похожие вопросы
Предмет: История,
автор: dvafina06
Предмет: Русский язык,
автор: vov4ik15382
Предмет: Математика,
автор: krupenkonika
Предмет: Математика,
автор: oliesia109
Предмет: Геометрия,
автор: nastiavadim1